Antioxidant, antiaging and mitochondrial protective effects of JadeAging in Caenorhabditis elegans - Lu, Bowen; Yin, Dongli; Zhang, Jiahao; Wang, Yilei; Wang, Xue; Zou, Shengcan; Li, Jiacheng (Frontiers in Pharmacology, 2026)
ObjectiveThis study aims to evaluate the antioxidant, anti-aging, and mitochondrial protective effects of JadeAging, a Chinese medicine-based longevity formulation, using the model organism Caenorhabditis elegans.MethodsWe used C. elegans to assess the impact of JadeAging and its individual components (rehmannia, poria, and ginseng) on various health metrics. RNA sequencing (RNA-seq) was performed to identify differentially expressed genes and their effects on biological pathways. Lifespan and healthspan assays were performed to evaluate cell vitality, whereas mitochondrial health was assessed using mitochondrial fragmentation analysis. Antioxidant capacity was determined by measuring protection against reactive oxygen speciesResultsTreatment with JadeAging did not significantly extend lifespan but showed improvements in healthspan, with treated animals exhibiting more vigorous movement over their lifespan. JadeAging and its components demonstrated significant antioxidant capacity, protecting C. elegans from the deleterious effects of paraquat-induced oxidative stress. Furthermore, JadeAging treatment significantly reduced mitochondrial fragmentation, indicating enhanced mitochondrial health. RNA-Seq data revealed downregulation of daf-2 and rsks-1 and upregulation of cpr-1, suggesting the activation of the Target of Rapamycin pathway and promotion of autophagy.ConclusionJadeAging exerts protective effects against oxidative stress and age-related mitochondrial decline, likely by modulating key longevity pathways. These findings support the positive effects of JadeAging and its components on health.